Occurrence of Panstrongylus megistus (Burmeister, 1835) in an area under entomological surveillance in the Southeast Region of Brazil - João Victor Leite Dias; Rita de Cássia Moreira de Souza; Janice Maria Borba Souza; Liléia Gonçalves Diotaiuti; Raquel Aparecida Ferreira (Revista da Sociedade Brasileira de Medicina Tropical, 2020)
Abstract INTRODUCTION: Panstrongylus megistus is the main triatomine involved in the human transmission of Trypanosoma cruzi in Minas Gerais, Brazil. We analyzed the occurrence of triatomines in the Itaúna micro-regions for healthcare. METHODS: Data were collected as part of routine entomological surveillance activities, including the species identity, capture site, developmental stage, and trypanosome infection. RESULTS: In total, 503 specimens from five species were captured (495 P. megistus). Adults were mainly captured by residents inside their homes, whereas nymphs were mostly captured by public health professionals outside. CONCLUSIONS: The epidemiologically important triatomine, P. megistus, continues to persist in our study region.